A extensão universitária e a formação profissional em cursos de graduação em saúde - Porto, Vanessa Fernandes de Almeida (2017)
The outreach experience reveals to be fundamental in academic education, allowing various experiences to students, beyond those obtained through the banking conception of professional qualification. This graduate thesis consists of one scientific article from a research developed in the work field of a master's student and a technical product themeoriented. The study that generated the scientific article aimed to analyze how the university outreach is constituted in undergraduate health academic education of a public higher education institution in Alagoas state. This is a cross-sectional study with a quantitative approach and non-probabilistic sampling. 411 students participated in the study, from 05 health undergraduate majors, who answered to an instrument composed by questions related to the student profile identification and 04 validated and adapted scales according to the study goal. Data analysis was performed by descriptive statistics, frequency per item, factor, class and undergraduate major. It was identified that 301 of the participants were female, representing the majority of the interviewees. The sample was equally distributed among the majors, being 115 from Medicine, 87 from Physical Therapy, 80 from Nursing, 75 from Speech-Language Pathology, and 54 from Occupational Therapy. 315 students informed that participate in community outreach activities, being 247 in academic leagues, while only 11 students participate in programs and 46 in projects. It was verified that university outreach consists as an important activity in health undergraduate student education, since it presents high expectation in applying knowledge that was taught in university outreach activities, as well as feeling motivated to apply them to their academic education and professional performance. The aspects that need to be observed to improve the university outreach politics and to broaden academic participation were also identified. From these results, one product was developed: Reflexive Feedback to managers and student representatives about the research results and formulation of intervention proposals to be implemented within the scope of outreach activities, at UNCISAL. The workshop was constituted as an important strategy for reflection about outreach activities, since participants demonstrated the need and wish that there were spaces like that regularly, therefore improving the university outreach activities.